EPIDEMIOLOGY OF COVID-19 CASES IN THE KLATEN DISTRICT IN 2020 - Wandhan Ayu Puspitaningrum; Nurussyifa Afiana Zaen; Chatarina Umbul Wahjuni (Universitas Airlangga, 2022)
Background: Coronavirus Disease 2019 (COVID-19) is an infectious disease caused by a new type of coronavirus, and as of September 11, 2020, 210,940 cases have been reported spread across all provinces in Indonesia. Central Java is the province with the 3rd highest cumulative case as of August 24, 2020. On the other hand, Klaten District ranks 11th out of 35 Districts/Cities in Central Java, and it is classified as a moderate risk zone area. Purpose: This study aims to describe the Covid-19 cases in Klaten District. Methods: This study was a descriptive observational study with a cross-sectional design. The data used secondary data obtained from the Covid-19 Case Report by the Surveillance, Health Quarantine, and Immunization Section of the Klaten District Health Office from March to August 2020. The population of all Klaten District people identified as positive for Covid-19 from March to August 2020. Samples were taken by using the total population sampling technique. Data analysis was presented using univariate analysis in narrative form, tables, charts, and distribution maps processed with health-mapper software. Results: Most Covid-19 cases occurred in men (50.31%). The highest confirmed cases happened in the productive age (49.06%), namely between 15-44 years. The area with the most confirmed cases was Wonosari Sub-district, with 72 confirmed cases. Covid-19 confirmed cases increased significantly in August with 180 confirmed cases. Conclusion: Klaten District is one of the areas affected by the Covid-19 pandemic with the number of cases that tends to increase since March to August 2020.